Increasing Passenger Satisfaction with the Quality of Terminal Facilities, Services and the Influence of Waiting Times and Prices - Joan Brilliand Ginting; Pamuraharjo, Hemi (International Journal of Integrative Sciences, 2024)
Previous research or relevant research is very important in a research or scientific article. Previous research or relevant research serves to strengthen the theory and phenomena of relationships or influences between variables. This article reviews the factors that influence Aircraft Passenger Satisfaction, namely the Quality of Terminal Facilities, the Quality of Service and the Effect of Waiting Time and Price on an Aircraft Passenger Service Quality literature study. The purpose of writing this article is to build a hypothesis of the influence between variables to be used in further research. The results of this literature review article indicate that there is (1) an influence of the quality of terminal facilities on Aircraft Passenger Satisfaction, (2) an influence of Service Quality on Aircraft Passenger Satisfaction, and (3) an influence of Waiting Time and Price on Aircraft Passenger Satisfaction